PERJANJIAN BAKU MENURUT PRINSIP SYARIAH (Tinjauan Yuridis Praktik Pembiayaan di Perbankan Syariah) - Fidhayanti, Dwi (Fakultas Syariah, 2014)
Nowadays many economic transactions conducted through the bank. In Indonesia, the banks can be divided into two, namely conventional banks and Islamic banks. The development of financing in Islamic banks illustrates that this product enjoyed by many people. To that end, the Islamic banking is necessary to a healthy financial services and in accordance with Islamic principles. This paper aims to assess How raw agreement according to Islamic principles and what the legal consequences of raw agreement on financing in Islamic banking for the parties. This paper uses the type of normative research to conduct legal interpretation of the material to obtain a solution to the problem. Results and discussion shows that raw raw agreement has been made legally, but do not pay attention to one of the Islamic principles set out in the acceptance of products and product distribution of funds in Islamic banking, the balance (tawÃ¢zun). Standard contract after an analysis according to Islamic principles, including the damaged or imperfect agreement because the agreement has been made legally, but there is one principle which is not fulfilled then make the agreement unenforceable. imperfect agreement did not result in legal consequences for the parties